Karakteristik Ruang Jalan Melalui Metoda Analisis Kuantitatif Untuk Arahan Rancang Kawasan Pariwisata di Pusat Kota Semarapura - Ni Wayan Nurwarsih; I Wayan Wirya Sastrawan; Ni Putu Ratih Pradnyaswari Anasta Putri (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2020)
Semarapura City offers a spatial layout in the City Center which is friendly to tourists who have limited visiting time and has the City Area into four areas with different functions known as Catuspata. In this research, the Catuspata area becomes the center of object orientation where the road space intended for the design direction of the tourism area will be along the road space. How will the strategic potentials in the development of a tourist city, city structure and tourism area as well as road space in the form of street floors and street walls will be defined. The method used is quantitative by collecting data on physical objects in the field objectively, then measuring it with predetermined variables and displaying it in numerical form, then doing a rationalistic analysis. The analysis is based on considerations of categorization, the uniqueness of the place, the shape and situation of the site, as well as certain functions. The results and findings are very visible, in the form of a new form of Semarapura city which is no longer a royal city due to changing activities and needs of the community. The interest of the street space where the trade is more oriented for tourists. The findings from the visual point of view of the area resulted in the solid-void faÃ§ade characteristics, rhythm and openings that had an effect on the quality of road space. Thus, the analysis of the structure of the city, building variables, street furniture and tourism activities that occur are findings from the characteristics of the road space which can serve as a direction for how the planning of the city's tourism area is made.